Persepsi Fairness Atas Sistem Evaluasi Kinerja - Adwita Harefa; Se Tin (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2021)
Abstract This study aims to determine performance evaluation system and fairness perception in performance evaluation system in manufacturing, merchandising and service business. The data acquisition was done using a survey method across company staffs over Sumatera, Java, Kalimantan, Sulawesi and Papua. Performance evaluation system is an essential component in a company’s financial and non-financial performance. This study shows that there are still perception gaps among manufacturing, merchandising and service business regarding procedural fairness for performance evaluation system. The result suggests company managements to consider a fair performance evaluation system in order to minimize conflict and tension while increasing both sense of justice and employee satisfaction in performance evaluation. Keywords: performance evaluation system, fairness perception